EKSISTENSI PROFITABILITAS STRATEGI INVESTASI MOMENTUM DI BURSA EFEK INDONESIA - Najmudin Najmudin (Faculty of Economics and Business Universitas Jenderal Soedirman, 2009)
The goal of this research is to test the existence of winner-loser anomaly based on underreaction hypothesis, specifically to investigate the profitability of momentum investment strategy in Indonesia Stock Exchange (IDX) by observing a sample of the firm listed at LQ45 index. For examining the presence of momentum in prices, the research used a variable of excess return from June 2004 to June 2007, and overlapping six months formation and test period.The analysis found that underreaction occured in the market, and there was strong evidence for price momentum of past winners and losers in IDX. On the other word, momentum investment strategy obtained significant profit for short-term horizon (six months). If momentum returns in United States and European markets were due to underreaction to information contained in past prices, this research found the same behavioral phenomenon in the Indonesian capital market.